Zeolites as Adsorbents and Photocatalysts for Removal of Dyes from the Aqueous Environment - Marina Rakanović; Andrijana Vukojević; Maria M. Savanović; Stevan Armaković; Svetlana Pelemiš; Fatima Živić; Slavica Sladojević; Sanja J. Armaković (Molecules, 2022)
This study investigated the potential of zeolites (NH4BETA, NH4ZSM-5, and NaY) to remove two frequently used dyes, methylene blue (MB) and rhodamine B (RB), from an aqueous environment. The removal of dyes with zeolites was performed via two mechanisms: adsorption and photocatalysis. Removal of dyes through adsorption was achieved by studying the Freundlich adsorption isotherms, while photocatalytic removal of dyes was performed under UV irradiation. In both cases, the removal experiments were conducted for 180 min at two temperatures (283 K and 293 K), and dye concentrations were determined spectrophotometrically. Additionally, after photodegradation, mineralization was analyzed as chemical oxygen demand. A computational analysis of the structures of MB and RB was performed to gain a deeper understanding of the obtained results. The computational analysis encompassed density functional theory (DFT) calculations and analysis of two quantum-molecular descriptors addressing the local reactivity of molecules. Experimental results have indicated that the considered zeolites effectively remove both dyes through both mechanisms, especially NH4BETA and NH4ZSM-5, due to the presence of active acidic centers on the outer and inner surfaces of the zeolite. The lowest efficiency of dye removal was achieved in the presence of NaY zeolite, which has a lower SiO2/Al2O3 ratio. A more efficient reduction was completed for RB dye, which agrees with the computationally obtained information about reactivity.